Comparing provider payment adjustments across 20 countries during COVID-19. (20th October 2021) - Waitzberg, RW; Quentin, W; van Ginneken, E; ,
Abstract: COVID-19 has affected health providers economically in two main ways. First, some providers lost income due to postponed services or patients refraining from seeking care. Second, other providers took on new tasks by treating (high volumes of) COVID-19 patients. All providers faced higher costs due to new hygiene and distance requirements. We reviewed if and how countries have adjusted payments to health providers during 2020 using an analytical framework and data from 20 countries. The analysis is based on information collected in the COVID-19 Health System Response Monitor (HSRM) and complemented by grey literature by country representatives who are experts on health policy and have reported the developments and responses to the pandemic since is very onset. We found that payments were not adjusted for many providers whose income did not depend on activity such as salaries, capitations and budgets. Most of the compensatory payments were in the form of new salaries and budgets that substituted activity-based payments, and some higher fees to compensate for activity shortfalls. New FFS payments were created to incentivize virtual services. Payments for COVID-19 related costs included mainly new fees for services. Hospitals also received new budgets to cover the costs of adjusting wards, creating new (ICU) beds, and hiring more workforce. Some countries also created new per diem and DRG tariffs to pay for COVID-19 patients. Consumables such as personal protective equipment and hygiene material were provided in-kind or reimbursed in-cash. Overall, governments bore many COVID-19 financial risks. Payment adjustments should be carefully designed in order to protect providers from income shortfalls without undermining productivity, access or quality of care. Payments for COVID-19 services should promote provision without leading to overtreatment or overspending.